2013
DOI: 10.1016/j.jmoldx.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Lung Cancer Histological Types by RT-qPCR Gene Expression in FFPE Specimens

Abstract: Lung cancer histologic diagnosis is clinically relevant because there are histology-specific treatment indications and contraindications. Histologic diagnosis can be challenging owing to tumor characteristics, and it has been shown to have less-than-ideal agreement among pathologists reviewing the same specimens. Microarray profiling studies using frozen specimens have shown that histologies exhibit different gene expression trends; however, frozen specimens are not amenable to routine clinical application. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…Similar results were obtained by Wilkerson and colleagues, who demonstrated a predictor comprising 51 unique genes [34]. They reported the prediction accuracy to stand at the level of 84%, as estimated by the Monte Carlo cross-validation procedure.…”
Section: Discussionsupporting
confidence: 84%
“…Similar results were obtained by Wilkerson and colleagues, who demonstrated a predictor comprising 51 unique genes [34]. They reported the prediction accuracy to stand at the level of 84%, as estimated by the Monte Carlo cross-validation procedure.…”
Section: Discussionsupporting
confidence: 84%
“…Previous ADC-SCC gene signatures have been reported (4146) and about 10–45% of the genes in these signatures overlap with ours. Two of these signatures were formally developed as classifiers, with external tumor set validation.…”
Section: Discussionsupporting
confidence: 82%
“…The resulting prediction had an accuracy of 92% (sensitivity: 99%, specificity: 84%) while our Classifier showed 95% accuracy (97% sensitivity, 93% specificity). The second study, from Wilkerson et al (46), had 15 genes (4 overlapping with our signature) and a reported prediction accuracy of 81% in external validation. Using the TCGA validation test, this corresponded to an accuracy of 92% (sensitivity: 90%, specificity 95%).…”
Section: Discussionmentioning
confidence: 98%
“…Multiple data sets, comprising 2177 samples, were assembled to evaluate a previously published 57-gene LSP gene-expression classifier. 21 The data sets included several publically available lung cancer gene-expression data sets, including 2099 FF lung cancer samples (The Cancer Genome Atlas [TCGA, Bethesda, Maryland], 15,16 University of North Carolina [Chapel Hill], 19,20 National Cancer Institute (NCI, Bethesda, Maryland), 22 25 and Duke University [Durham, North Carolina] 26 ), as well as newly collected geneexpression data from 78 FFPE samples. 27 Data sources are provided in Table 1, including normalization methods applied to each data set.…”
Section: Methodsmentioning
confidence: 99%
“…This method can thus be used to assist the pathologist in classifying lung tumors. 21 In this study, the ability of the LSP gene signature to reliably subtype lung tumor samples using gene expression data from any one of multiple platforms, including Affymetrix (Santa Clara, California) and Agilent (Santa Clara, California) DNA microarrays, RNA sequencing, and quantitative reverse transcription-polymerase chain reaction (qRT-PCR), was investigated.…”
mentioning
confidence: 99%